Cost of Sales of Seaweed Cracker (Case Study in Benteng Village, Palopo City) - Tajufri, Ardillawati; Hasani, M. Chasyim; Fakhriyyah, Sitti; Cangara, Arie Syahruni; Gosari, Benny Audy Jaya (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
The development of the business world is growing and the type of business is growing because most individuals choose to open their own businesses, especially in the field of micro, small and medium enterprises (MSMEs) because they do not require large capital. Benteng Village is one of the areas where there are product processing business activities by utilizing seaweed fishery resources (E.Cattoni/K.Alvareii) as one of the raw materials. Seaweed E. Cattoni is one type of seaweed that can be used in various food and beverage products because it has properties that do not reduce the delicacy of food, in addition, E. cottoni seaweed is known as a source of fiber so that it can be used in making crackers. . Crackers are one of the snacks that are consumed as a snack or as a complementary food to regular meals. The purpose of this study is to determine the cost of goods sold in seaweed cracker business X. To achieve this goal, the survey method is used, where survey research is research that takes samples from a population in the field by conducting direct observations at the research site, through interviews and interviews. observation of respondents and using questionnaires as a data collection tool that had been prepared in advance by the researcher. The results of this study indicate that the calculation of the cost of goods sold in the seaweed cracker business X obtained results of Rp. 10,000/product and the cost of production of Rp. 4,171/product so that the profit per product is Rp. 5,829.